An Experimental Study on the Control of Slotless Self-Bearing Motor Using Nonlinear Control - Nhan, V. D.; Bien, N. X.; Dich, N. Q.; Ha, V. T. (Engineering, Technology & Applied Science Research, 2022)
This article presents a Slotless Self-Bearing Motor (SSBM) with a six-phase coil stator instead of an iron core. The rotor consists of a permanent magnet and an encased iron yoke. The magnetic forces caused by the interplay between the stator currents and the magnetic field govern the rotational speed and radial position of the rotor. An SSBM mathematical model and its control method are also included in this study. This motor is controlled by field-oriented control. Theoretical analysis of magnetic force and moment characteristics is performed, and a control approach is provided. Sliding-mode control is a control technique that is simple, and effective and is used to assist the control system in approaching the reference value. It is also widely utilized to control the position and speed of the motor. The findings were constructed and validated using experiment-confirmed analytical data to prove the proposed control strategy.